2012
DOI: 10.1038/ejcn.2012.44
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long-term intake of lactotripeptides on cardiovascular risk factors in hypertensive subjects

Abstract: BACKGROUND/OBJECTIVES: Lactobacillus helveticus LBK-16H-fermented milk products containing tripeptides isoleucine-prolineproline and valine-proline-proline lower blood pressure in hypertensive subjects using office and home blood pressure registration. The present study was aimed to evaluate the effects of two doses of these lactotripeptides on 24-h ambulatory blood pressure and lipidomics profiles in mildly hypertensive subjects. SUBJECTS/METHODS: In a randomized, double-blind, placebo-controlled parallel gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 37 publications
0
23
0
1
Order By: Relevance
“…The differences between the treatment group and the placebo group were not statistically significant, but the authors concluded that the observed effect may have clinical significance (Jauhiainen et al, 2010, 2012). In addition, Usinger et al (2010) recently reported that LhFM (strain Cardi04) did not inhibit ACE in humans.…”
Section: Ace Inhibitory Activitymentioning
confidence: 98%
“…The differences between the treatment group and the placebo group were not statistically significant, but the authors concluded that the observed effect may have clinical significance (Jauhiainen et al, 2010, 2012). In addition, Usinger et al (2010) recently reported that LhFM (strain Cardi04) did not inhibit ACE in humans.…”
Section: Ace Inhibitory Activitymentioning
confidence: 98%
“…Milk peptides are beneficial in treating MS [109] . A dose response study showed insignificant reductions in BP [110] . The clinical response is attributed to fermented milk's active peptides which inhibit ACE.…”
Section: Proteinmentioning
confidence: 99%
“…Bovine casein-derived peptides and whey protein-derived peptides exhibit ACEI activity [102][103][104][105][106][107][108][109][110][111] . These components include B-caseins, B-lg fractions, B2-microglobulin and serum albumin [102][103][104]111] .…”
Section: Proteinmentioning
confidence: 99%
“…51 A comparison of patients with low and high HDL-C identified novel cis-expression quantitative trait loci variants in the human leukocyte antigen region associated with low HDL-C. 40 Low HDL-C subjects were found to have elevated TG and diminished lyso-phosphatidylcholine and sphingomyelin. 53 Studies on dietary habits 47,49,55,56 and obesity 57-61 also compared the lipid composition. For example, increased concentrations of TG with long FA chains and ceramides, specifically ceramides (d18:1/24:1), correlated with macrophage infiltration in subcutaneous adipose tissue in subjects with high liver fat content.…”
Section: Applications Of Lipidomics To Clinical Cohortsmentioning
confidence: 99%
“…[33][34][35][36][37][38][39][40] A summary of the studies is presented in Table 3. Lipid profiling has shown promising results in diabetes mellitus, [41][42][43][44][45][46][47] CVDs, 35,37,38,48-52 metabolic disorders, 40,53,54 dietary habits, and obesity, 47,49,[55][56][57][58][59][60][61] as well as in determining response to drug therapy. [62][63][64][65] Most studies analyzed either blood or tissue samples (ie, diabetic retinopathy, 46 atherosclerotic plaques, 52 muscle, 47 or adipose tissue).…”
Section: Applications Of Lipidomics To Clinical Cohortsmentioning
confidence: 99%